Development of Research-Based Modules in Hydroponic Learning - Mellisa; Rahmi, Laili; Yeyendra; Waltriandi, Yandri; Puspita Sari, Anggun (Journal Of Biology Education Research (JBER), 2025)
Hydroponics is an increasingly popular cultivation method due to its land and water use efficiency. To support students' understanding in this field, a research-based learning module is needed to ensure that the material presented is relevant and evidence-based. An interactive and research-based learning module can enhance students' conceptual understanding and skills in effectively applying hydroponic techniques. This study aims to develop a hydroponic module based on research results. This study utilizes the ADDIE model in the module development phase, students' needs and curriculum requirements were identified to align the module content with learning objectives. The design phase involved structuring the module by integrating recent research findings in hydroponics, selecting appropriate instructional strategies, and incorporating interactive elements. In the development phase, the module was created with interactive features and media to enhance engagement and comprehension. The implementation phase included pilot testing with students to gather feedback on usability and effectiveness. Finally, in the evaluation phase, expert validation and student assessments were conducted to measure the module's validity and effectiveness. Trials and validation were conducted by experts, including media specialists, subject matter experts, and hydroponic practitioners, to ensure the module met quality standards. Validation results indicated that the developed module was categorized as highly valid. Additionally, based on student assessments, the module received in the "good" category, demonstrating its suitability for hydroponics courses. These findings suggest that the research-based hydroponics module is an effective learning resource for students, providing both theoretical knowledge and practical applications in hydroponics education.